FACTORS INFLUENCING THE WORK PERFORMANCE OF ASHA UNDER NRHM A CROSS SECTIONAL STUDY FROM EASTERN UTTAR PRADESH - Kumar, Santosh; Kaushik, Amit; Kansal, Sangeeta (Indian Journal of Community Health, 2012)
Research question: What are the factors influencing the work performance of ASHA? Objectives: To study the factors influencing the work performance of ASHA in community. Study Design: Descriptive cross sectional study. Setting: The present study was conducted in the field practice area of Rural Health & Training Centre of Institute of Medical Sciences, Banaras Hindu University, Varanasi. Participants: One hundred and thirty five ASHAs were included in the present study. Material and Methods: A cross sectional study was conducted based on a sample of 135 ASHAs working in different areas of Chiraigaon Block of Varanasi district in eastern Uttar Pradesh (UP). ASHAs were interviewed for their functioning and their outcome was correlated. Chi-square test was used to analyze the data. Results: The study revealed that only 16.3% ASHAs knew about motivating the community for toilet construction. Twenty three percent ASHAs were aware that they should also give medical care for minor ailments. Their less knowledge for content of responsibility significantly affected their practices in community. The practices of the more knowledgeable group were found better than the ignorant one. Conclusion: Less knowledge of the content of job responsibility, caste, incentive oriented practices and delayed and inadequate payment of incentives for ASHAs influences the work performance.